Benefício de aposentadoria por idade ao segurado especial: o trabalhador rural no Sistema de Previdência Social brasileiro - Gomes, José Ary de Souza (2024)
The dissertation developed here discusses the characteristics necessary to prove and grant the retirement of the special insured involving rural producers and artisanal fishermen. The focus is mainly aimed at rural producers. The special insured is entitled to the old-age retirement pension benefit. To do so, the farmer must be 55 years old if a woman, and 60 years old if a man, in addition to proving 15 years of rural activity through documents. In this study, the objective is to understand the causes/reasons that lead to the denial of the concession due to the failure to prove the legal requirements for the right to retirement benefits, to characterize the special insured and to identify the specific characteristics of their retirement. The research concludes that the main causes that lead to the refusal to grant the retirement benefit are the difficulty in proving the necessary time of rural activity and proving the particularities that make the rural producer characterized as a special insured, based on what establishes the legislation. In 9 chapters, the dissertation presented is a qualitative scientific research (whose collected data provide details and depth of knowledge for a better understanding of the implications revealed), of an exploratory nature (its emphasis is on the subjective character of the object, on the study of their particularities and unique experiences) and guided by the analytical-descriptive narrative, as it uses comparison, history, legislation and jurisprudence, accompanied by empirical data